BA302: Microsoft Dynamics NAV ERP Exercise/Walkthrough - Curry,Michael; Marshall,Byron; Raja,V.T.; Reitsma,Reindert; Wydner,Kirk (2016)
Whether you enter the workforce as a sales manager, financial accountant or office admin, chances are that you will be working with some type of Enterprise Resource Planning (ERP) system. The purpose of this exercise/walkthrough is to familiarize you with a typical business process as it is commonly executed with the help of one of the leading ERP systems in the market today – Microsoft Dynamics NAV. This exercise will walk you through the six steps of a typical sales process: 1) Creating a customer order; 2) Backordering an out-of-stock item; 3) Receiving the backordered item; 4) Shipping the customer the ordered items and invoicing the customer; 5) Receiving payment from the customer; 6) Making a payment to the vendor from whom we backordered. As you make your way through this exercise, you should realize that in a real company this process would be executed by different people working in different departments. They all will interact with the ERP; i.e., they all retrieve information from the ERP and store new information in it, as the sales process progresses. In this exercise you take on the role of each of these people, giving you a sense of how the sales order is processed both by the company and by the ERP.
Keywords: Accounting; BIS